Schooling in East Asia : forces of change : formal and nonformal education in Japan, the Republic of China, the People's Republic of China, South Korea, North Korea, Hong Kong, and Macau - Thomas, R. Murray (Robert Murray), 1921-2016; Postlethwaite, T. Neville (Pergamon Press, 1983)
Schooling in East Asia: Forces of Change describes the condition and backgrounds of formal and non-formal education in five East Asian nations and in two colonies. The book also considers the forces that have influenced the form that the seven educational systems have assumed. Organized into nine chapters, this book begins with an identification of the several significant historical features of East Asia. The next seven chapters are presented in four parts. Part I centers on Japan, Part II on the Republic of China on Taiwan and the People's Republic of China on the Asian mainland, Part III on.